Penguatan Proses Pengajaran Thaharah Cara Berwudhu di MADIN Miftahul Ulum Kesugihan - Febri Sapitri; Diyan Putri Ayu (Social Science Academic, 2023)
This research is in the background of how important the teaching of ablution is in Madrasah Diniyah Miftahul Ulum Kesugihan Pulung Ponorogo, where the environment still holds the jawen Islam. The child already knows the ablution, but if the child is asked to practice the steps of the wudhu, the child often does not sequence according to the steps of the ablution and even sometimes the child forgets one of the steps. The selection of the " ablution " method because as Muslims pray is an obligation to do, without proper ablution, then prayers are not valid. Therefore, to facilitate learning for children, researchers will use a direct learning strategy. This study aims to: 1) describe the process of implementing learning in improving the ability to know the bersudhu method through direct learning strategy and 2) grow up that the direct learning strategy can improve the take ablution methodology in Madrasah Diniyah Miftahul Ulum Kesugihan children. This study used classroom action research method in collaboration with madin teachers. The subjects of his research were several Madin children and one madin teacher, after which data were collected using observation and test techniques, then quantitatively analyzed.The results of several studies conducted by some madam children were 57% in the first cycle while in the second cycle it was 93%. Thus, it can be concluded that direct learning strategies can improve children's ability in the manner of "wudhu" in the early madrasah of Miftahul Ulum. It is recommended to Madin, the next teacher and researcher to use direct learning strategies to improve the ability to know other gobudhu manners.